2021
DOI: 10.1016/j.jsams.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Bifactor structure and model reliability of the Test of Gross Motor Development — 3rd edition

Abstract: Objectives: This study investigated the structure of the Test of Gross Motor Development -3rd edition (TGMD-3). Specifically, we examine bifactor structure, which simultaneously models a fundamental motor skills (FMS) general factor and specific factors for locomotor skills and ball skills, compared to other models. Design: Cross-sectional design using the TGMD-3 normative sample. Methods: The sample (N = 862) of children (Mage = 6.51, SD = 2.23) was matched based on United States census data, ensuring appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The sixth and last category includes two constructs that did not fit the aforementioned five domains: motoric skills (Garn and Webster, 2021 ) and scar evaluation (Sen et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sixth and last category includes two constructs that did not fit the aforementioned five domains: motoric skills (Garn and Webster, 2021 ) and scar evaluation (Sen et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that for both boys and girls, the FMS of children, measured based on the second test of gross motor development (TGMD-2), showed significant differences before and after the summer vacation. Therefore, a regular teaching cycle (16 weeks) was selected in this study to meet the theoretical needs of constructing a cross-lag model [19]. Considering the actual needs of the test, the second week of school and the second or third week before the summer vacation were selected for tests T1 and T2, respectively, without affecting the normal teaching order.…”
Section: Methodsmentioning
confidence: 99%
“…It has good stability and validity and can be used as a tool to assess the development of FMS in children aged 3-10 years in China [24]. The TGMD series is currently one of the most widely used FMS evaluation tools worldwide [19]. In this study, the TGMD operating specifications were strictly followed.…”
Section: (1) Physical Activitymentioning
confidence: 99%
“…Fundamental motor skill levels have been investigated for children worldwide using the various versions of the Test of Gross Motor Development [ 10 ]. The psychometrics of the TGMD-3 have been investigated in the United States [ 11 , 12 ], Brazil [ 13 , 14 ], Germany [ 15 ], Iran [ 16 ], Persia [ 17 ], Bosnia and Herzegovina [ 18 ], Spain [ 19 ], Italy [ 20 ], Canada [ 21 ], Greece [ 22 ] and Ireland [ 23 ]. The results provide relevant information about TGMD-3-appropriate indexes of reliability [ 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 , 24 , 25 ] and factorial structure [ 13 , 14 , 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The psychometrics of the TGMD-3 have been investigated in the United States [ 11 , 12 ], Brazil [ 13 , 14 ], Germany [ 15 ], Iran [ 16 ], Persia [ 17 ], Bosnia and Herzegovina [ 18 ], Spain [ 19 ], Italy [ 20 ], Canada [ 21 ], Greece [ 22 ] and Ireland [ 23 ]. The results provide relevant information about TGMD-3-appropriate indexes of reliability [ 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 , 24 , 25 ] and factorial structure [ 13 , 14 , 18 , 21 ]. For the current third edition, the psychometrics of the TGMD-3 items and the motor performance criteria (i.e., include preparatory movement, body position during the action, and follow-through) have been investigated only in the American sample regarding differential item functioning for gender and race, and satisfactory correlations (values above 0.25) were obtained, showing the validity of the item’s discriminative power [ 6 ].…”
Section: Introductionmentioning
confidence: 99%